Prinsip Hukum Pengamanan Eksekusi Benda Jaminan Fidusia oleh Kepolisian Negara Republik Indonesia - Kukuh Sugiarto Kurniawan (JURNAL RECHTENS, 2013)
Indonesian National Police are in charge of the state apparatus and serves to maintain security and public order, law enforcement, protection, guidance, and service to the community. Police of the Republic of Indonesia as a country that is authorized to provide security assistance in the implementation or execution of court decisions fiduciary. The fiduciary safeguards provisions contained in the Police Regulation No.8 of 2011. Police Regulation No.8 of 2011 as a guideline for the Indonesian National Police to secure the execution of fiduciary. Fiduciary execution is an integral part of the law of civil procedure, so the Police Regulation 8 of 2011 must not be contrary to the law of civil procedure.